2021
DOI: 10.1186/s40814-021-00815-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to fidelity in a pilot trial of individualized resistant starches for pediatric inflammatory bowel disease: a fidelity study protocol

Abstract: Background The consumption of resistant starches is a promising adjuvant therapy for patients with inflammatory bowel disease. Rigorous evaluation of resistant starches in this setting depends on the intervention being delivered, received, and enacted as intended, that is, with fidelity. As part of a planned pilot trial, participants will be randomized to ingest resistant starches or a placebo. They will also be asked to collect stool samples and keep symptom and dose diaries to inform trial ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…As a result of CD develops progressively in the way of remission-relapse-remission, CD patients often have frequent demands for medical services such as multiple operations, routine reexamination, medical treatment, which will increase patients' dependence on their main caregivers to accompany them to seek medical treatment and provide daily care [ 26 ]. Bedford's study have shown that the level of stoma acceptance of patients is significantly related to the time after colostomy [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of CD develops progressively in the way of remission-relapse-remission, CD patients often have frequent demands for medical services such as multiple operations, routine reexamination, medical treatment, which will increase patients' dependence on their main caregivers to accompany them to seek medical treatment and provide daily care [ 26 ]. Bedford's study have shown that the level of stoma acceptance of patients is significantly related to the time after colostomy [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive description of the methods of the present study can be found in the study protocol [ 12 ]. It was originally planned that the present study would include only participants and caregivers of the RSP trial.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed trial information on both trials can be found on the clinical trials registry (https://clinicaltrials.gov RSP Identifier: NCT0452227; MEND Identifier: NCT04520594). A comprehensive description of the methods for the present study can be found in the study protocol (11). It was originally planned that the present study would include only participants and caregivers of the RSP trial.…”
Section: Setting and Participantsmentioning
confidence: 99%